A preliminary study of phonological development in Kelantan children aged 2 to 5 years old - Wahid, Wan Zaharah Ab; Ghani, Azlinda Abd (2002)
Estimated ages of phonemes acquisition is vital as a baseline in making accurate diagnosis for children with phonological disorders and also useful for the speech remediation program.This preliminary study of phonological development aimed to determine the ages of acquisition of 17 phonemes in the Kelantanese dialect and comparison was made between these acquisition ages among English,Arabic and Cantonese children.Samples were obtained from a hundred normal developing Kelantanese children between the ages of 2 to 5.A structured and formal picture-naming test, consist of 35 single word that representing phonemes at all possible initial middle and final positions in Malay Kelantanese Dialect was used.Speech sample was recorded on a portable cassette recorder and were transcribed using the International Phonetic Analysis system (IPA).Subject was considered to master target phoneme when she or he produced it at least 85% correct at initial, middle or final position. It was noted that by the age of 3, subjects have acquired at least 8 phonemes.Among the earliest phoneme to be mastered is the unvoiced stop/p/and the last phoneme to be acquired is the fricative /s/.These findings also support Jakobsen's universal theory.The ages of acquisition of phonemes among Kelantanese children was quite similar to those for English and Arabic but was relatively delayed from Cantonese.